Red land, black land daily life in ancient Egypt - Mertz, Barbara (New York William Morrow, 2008)
An erudite and witty glimpse of the human side of ancient Egypt, this classic work is revised and updated for a new generation. Displaying the descriptive power, eye for detail, keen insight, and wit that have made her novels bestsellers, renowned Egyptologist Mertz transports us back thousands of years and immerses us in the sights, aromas, and sounds of day-to-day living in the legendary desert realm that was ancient Egypt. What did average Egyptians eat, drink, wear, gossip about, and aspire to? What were their amusements, their beliefs, their attitudes? Mertz ushers us into their homes, workplaces, temples, and palaces to show us the everyday worlds of the royal and commoner alike. We observe priests and painters, scribes and pyramid builders, slaves, housewives, and queens--and receive tips on how to perform tasks essential to ancient Egyptian living, from mummification to making papyrus.--From publisher description
Originally published: New York : Coward-McCann, 1966
Includes bibliographical references (p. [391]-396) and index
1
Keywords: Egypt -- Civilization -- To 332 B.C